Product Assortment With Sustainable Product Attributes: The Case of a Tire Producer - Sarigol, Ilkan; Bayraktar, Erkan; Ozkan, Coskun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
Relying on a real-life dataset collected from one of Turkey's top three tire producers, this study investigated a product assortment problem with sustainable product attributes. Since the economic aspect of sustainability predominates the environmental and societal ones, firms struggle to increase their sustainable products' market share in their portfolio. The article aims to identify the impact of sustainable consumer preferences, producer strategy for sustainability, and service level policies (SLP) on the number of assortments, profit, average sale prices, and out-of-stock level of tires. Consumer preferences based on sustainability attributes were calculated by a utility-based multinomial logistic regression. A mixed-integer linear programming model was developed to maximize profit with respect to inventory constraints and demand substitution rates under different producer sustainability targets (PST) and SLP. The results show that the producer's profitability and the number of assortments in the market tend to decrease as PST increases, which means that the producer produces a proportionally higher number of sustainable products. When consumers place their preferences according to only economic attributes, the tire producer has higher profitability and average sale prices than the consumers deciding with all-sustainability attributes. However, suppose the tire producer chooses to act proactively and aggressively launches more sustainable products. In that case, it may achieve higher profit margins than a market requesting more sustainable products in the long run. SLP of the tire producer had no significant impact on the number of assortments and average sale prices.
Keywords: Sustainable development; Tires; Economics; Costs; Industries; Portfolios; Planning; Consumer preferences (CP); multinomial logistic regression; product assortment; sustainability; ENVIRONMENTAL SUSTAINABILITY; AUTOMOTIVE PRODUCTS; VARIETY; CHOICE; OPTIMIZATION; DEMAND; SALES; METHODOLOGY; PERFORMANCE; PORTFOLIO; Business & Economics; Engineering